2023
DOI: 10.1186/s12902-023-01473-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between thyroid dysfunction, autoimmune thyroid disease, and rheumatoid arthritis disease severity

Mohammad Amin Yazdanifar,
Mahsa Bagherzadeh-Fard,
Mohammad Amin Habibi
et al.

Abstract: Background Rheumatoid Arthritis (RA) and autoimmune thyroid disease (AITD) are the two most prevalent coexisting autoimmune diseases due to their similar pathogenesis. Considering the potential effect of AITD on the severity of RA disease, this study aimed to determine the association between thyroid dysfunction, anti-thyroid peroxidase (anti-TPO) positivity, AITD, and RA disease severity in the Iranian population. Methods Three hundred and fifty R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…A cross-sectional study of 350 RA patients, looking at thyroid dysfunction as well as AITD assessed by the presence of ATA, found that thyroid dysfunction, TPOAb positivity, and AITD were significantly more common in RA patients with more severe disease activity measured using the DAS28-ESR. Positive TPOAb was more prevalent (OR 2.93) among patients with severe disease activity compared to those in remission [ 69 ].…”
Section: Effect Of Aitd On Ra Disease Activitymentioning
confidence: 99%
“…A cross-sectional study of 350 RA patients, looking at thyroid dysfunction as well as AITD assessed by the presence of ATA, found that thyroid dysfunction, TPOAb positivity, and AITD were significantly more common in RA patients with more severe disease activity measured using the DAS28-ESR. Positive TPOAb was more prevalent (OR 2.93) among patients with severe disease activity compared to those in remission [ 69 ].…”
Section: Effect Of Aitd On Ra Disease Activitymentioning
confidence: 99%